2015
DOI: 10.1007/s00415-015-7911-4
|View full text |Cite
|
Sign up to set email alerts
|

Powerhouse failure and oxidative damage in autosomal recessive spastic ataxia of Charlevoix-Saguenay

Abstract: Autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS) is a neurodegenerative disease due to mutations in SACS, which encodes sacsin, a protein localized on the mitochondrial surface and possibly involved in mitochondrial dynamics. In view of the possible mitochondrial involvement of sacsin, we investigated mitochondrial activity at functional and molecular level in skin fibroblasts obtained from ARSACS patients. We observed remarkable bioenergetic damage in ARSACS cells, as indicated by reduced ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 16 publications
8
45
0
Order By: Relevance
“…These observations combined with an increase in expression of oxidative stress gene transcripts demonstrate that mitochondrial health is reduced in ARSACS. This is in agreement with another very recent study that has also reported reduced bioenergetic function and oxidative stress in ARSACS (22). This study compared five patient and control HDFs and did not corroborate findings in any cellular models with isogenic controls (this was a key reason we also performed comparative analyses in sacsin knockdown cells).…”
Section: Discussionsupporting
confidence: 94%
“…These observations combined with an increase in expression of oxidative stress gene transcripts demonstrate that mitochondrial health is reduced in ARSACS. This is in agreement with another very recent study that has also reported reduced bioenergetic function and oxidative stress in ARSACS (22). This study compared five patient and control HDFs and did not corroborate findings in any cellular models with isogenic controls (this was a key reason we also performed comparative analyses in sacsin knockdown cells).…”
Section: Discussionsupporting
confidence: 94%
“…Several recent lines of evidence from patient cells, as well as from mouse models, suggest that sacsin acts as a chaperone or regulator for the organization of the intermediate filament cytoskeleton (Duncan et al, 2017). Sacsin deficiency thus leads to an altered organization of these intermediate filaments and-probably downstream-alterations in multiple mitochondrial functions, including mitochondrial fission (Girard et al, 2012), oxidative phosphorylation (Criscuolo et al, 2015), and oxidative stress pathways (Duncan et al, 2017). This might explain the partly ''mitochondrial clinical features'' observed in several ARSACS patients (such as, e.g., ophthalmoplegia, epilepsy, or hearing impairments).…”
Section: Disease Mechanism and Modelingmentioning
confidence: 99%
“…Autosomal recessive spastic ataxia of Charlevoix–Saguenay (ARSACS) is a neurodegenerative disorder, phenotypically characterized by walking difficulties and gait unsteadiness symptoms. The gene mutated and responsible for the pathology encodes for sacsin (SACS), a protein involved in mitochondrial network organization . It has been reported that ARSACS cells show bioenergetic and mitochondrial impairment, denoted by reduced respiratory chain activities and low mitochondrial ATP synthesis .…”
Section: Neurological Diseases Associated To Oxidative Stressmentioning
confidence: 99%
“…The gene mutated and responsible for the pathology encodes for sacsin (SACS), a protein involved in mitochondrial network organization . It has been reported that ARSACS cells show bioenergetic and mitochondrial impairment, denoted by reduced respiratory chain activities and low mitochondrial ATP synthesis . Sacsin is involved in interconnecting the mitochondrial network and contributes to their proper localization in neurons, and lack of sacsin induces a hyper fused mitochondrial phenotype and a balloon‐like morphology .…”
Section: Neurological Diseases Associated To Oxidative Stressmentioning
confidence: 99%